2010
DOI: 10.2172/1001442
|View full text |Cite
|
Sign up to set email alerts
|

How Do High Levels of Wind and Solar Impact the Grid? The Western Wind and Solar Integration Study

Abstract: NOTICEThis report was prepared as an account of work sponsored by an agency of the United States government. Neither the United States government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 2 publications
0
25
0
1
Order By: Relevance
“…Since power output of a wind farm is a function of the wind-speed, power generation can vary from timescales of less than a minute to several days or weeks [Lew et al, 2010]. The wind power industry thus needs accurate wind-speed forecasts for the timescale of several minutes to several years for a wide range of applications including turbine blade pitch control, conversion systems control, load scheduling, maintenance scheduling and resource planning [Stetsos, 2000;Costa et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Since power output of a wind farm is a function of the wind-speed, power generation can vary from timescales of less than a minute to several days or weeks [Lew et al, 2010]. The wind power industry thus needs accurate wind-speed forecasts for the timescale of several minutes to several years for a wide range of applications including turbine blade pitch control, conversion systems control, load scheduling, maintenance scheduling and resource planning [Stetsos, 2000;Costa et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Lew et al 4 studied the operational impact of up to 35% energy penetration of wind, photovoltaics (PVs), and concentrating solar power (CSP) on the power system in southwestern United States. They showed that it is operationally feasible to accommodate 30% wind and 5% solar energy penetration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most electrical grids are able to incorporate variable renewables when the penetration of renewables is small without the need for storage mechanisms 4 . When the penetration of renewables becomes large, some sort of storage mechanism becomes necessary.…”
Section: Estimating Wind and Solar Power Installations In Fy2022 Withmentioning
confidence: 99%
“…There are inherent challenges with increased penetration of variable generation sources like wind and solar, which can be addressed with increased balancing area cooperation and greater system flexibility (Lew et al, 2010). However, without broader cooperation and planning, these challenges can lead to peaking plants built predominantly to support intermittent renewable generation.…”
Section: New Physical Plantsmentioning
confidence: 99%